A retrospective evaluation of the epithelial changes/lesions and neoplasms of the Gallbladder in Turkey and a review of the existing sampling methods: A multicentre study - Esendağlı, Güldal; Akarca, Fahire Göknur; Balcı, Serdar; Argon, Asuman; Şengiz Erhan, Selma; Turhan, Nesrin; İnce Zengin, Neslihan; Hallaç Keser, Sevinç; Çelik, Betül; Bulut, Tangül; Abdullazade, Samir; Erden, Esra; et al. (Federation of Turkish Pathology Societies, 2018)
Objective: As there is continuing disagreement among the observers on the differential diagnosis between the epithelial changes/lesions and neoplasms of the gallbladder, this multicentre study was planned in order to assess the rate of the epithelial gallbladder lesions in Turkey and to propose microscopy and macroscopy protocols. Material and Method: With the participation of 22 institutions around Turkey that were included in the Hepato-Pancreato-Biliary Study Group, 89,324 cholecystectomy specimens sampled from 2003 to 2016 were retrospectively evaluated. The numbers of adenocarcinomas, dysplasias, intracholecystic neoplasms/adenomas, intestinal metaplasias and reactive atypia were identified with the review of pathology reports and the regional and countrywide incidence rates were presented in percentages. Results: Epithelial changes/lesions were reported in 6% of cholecystectomy materials. Of these epithelial lesions, 7% were reported as adenocarcinoma, 0.9% as high-grade dysplasia, 4% as low-grade dysplasia, 7.8% as reactive/regenerative atypia, 1.7% as neoplastic polyp, and 15.6% as intestinal metaplasia. The remaining lesions (63%) primarily included non-neoplastic polypoids/hyperplastic lesions and antral/pyloric metaplasia. There were also differences between pathology laboratories. Conclusion: The major causes of the difference in reporting these epithelial changes/lesions and neoplasms include the differences related to the institute’s oncological surgery frequency, sampling protocols, geographical dissimilarities, and differences in the diagnoses/interpretations of the pathologists. It seems that the diagnosis may change if new sections are taken from the specimen when any epithelial abnormality is seen during microscopic examination of the cholecystectomy materials.
Keywords: Gallbladder; Cholecystectomy; Dysplasia; Neoplasia; Sampling